Factors of Influence on Purchasing Behavior, A Model with Latent Variables - Franco, Héctor Hugo Mora; Higuera, Diego Israel Sanabria; Torres, Onier Alexander Pinto (Journal of Posthumanism, 2024)
The present study analyzes the factors that influence consumer purchasing behavior in shopping centers in five intermediate cities in Colombia (Cúcuta, Montería, Pasto, Tunja, and Villavicencio). A structural equation model based on partial least squares (PLS-PM) was utilized to assess the interaction among sociocultural, psychological, and marketing factors in regard to purchasing behavior. The data presented herein were collected through the implementation of a structured survey, which was administered to 1,750 consumers. The findings suggest that marketing factors exert the most substantial direct influence on purchasing behavior (β=0.662). The impact of sociocultural factors on psychological aspects is significant (β=0.431), and these factors, in turn, exert a notable influence on purchasing behavior (β=0.111). Marketing factors have also been demonstrated to exert an influence on psychological factors (β=0.269). The model accounts for 51.4% of the variance in purchasing behavior. The findings of this study offer valuable implications for commercial managers seeking to develop effective strategies that are adapted to the expectations of the contemporary consumer in the Colombian context.